New and little known species of Zorotypus Silvestri (Zoraptera: Zorotypidae) from China - Yin, Zi-Wei; Li, Li-Zhen; Wu, Chao (Zootaxa, 2015)
A new species of the insect order Zoraptera, Zorotypus hainanensis sp. n., is described from southern China based on apterous adults, which represents a fourth species of the genus in China. Additional collection data for Z. medoensis Hwang in Xizang (= Tibet) is provided. Illustrations of the major diagnostic features of both the new species and Z. medoensis are provided, and their taxonomic placements are briefly discussed.